The Effect of Entrepreneurial Orientation on the Competitive Advantage through Strategic Entrepreneurship in the Cafe Business in Ambon - Sesilya Kempa; Truly Gladys Setiawan (Petra International Journal of Business Studies, 2019)
The changed lifestyle of Ambon city residents influenced cafe business growth in Ambon. This research aims to determine the effect of entrepreneurial orientation on strategic entrepreneurship used by cafes and their impact on competitive advantage. The type of research used in this research is quantitative research using an accidental sampling technique. The data collection process was carried out by distributing 50 questionnaires to the owners or managers of cafes in Ambon. From 50 questionnaires that have been distributed, only 41 questionnaires (82% response rate) cn be processed further using partial least square (PLS) method. This research found out that entrepreneurial orientation affects strategic entrepreneurship, strategic entrepreneurship affects competitive advantage, and entrepreneurial orientation affects competitive advantage through strategic entrepreneurship. The magnitude of the influence of each is 0.724; 0.511; and 0.370. In this research, the entrepreneurial orientation of the owner and manager of the cafe did not affect the competitive advantage of the cafe at all.